2018
DOI: 10.1152/ajpendo.00261.2017
|View full text |Cite
|
Sign up to set email alerts
|

Significant improvement in cardiometabolic health in healthy nonobese individuals during caloric restriction-induced weight loss and weight loss maintenance

Abstract: Calorie restriction (CR) triggers benefits for healthspan including decreased risk of cardiometabolic disease (CVD). In an ancillary study to CALERIE 2, a 24-mo 25% CR study, we assessed the cardiometabolic effects of CR in 53 healthy, nonobese (BMI: 22-28 kg/m) men ( n = 17) and women ( n = 36). The aim of this study was to investigate whether CR can reduce risk factors for CVD and insulin resistance in nonobese humans and, moreover, to assess whether improvements are exclusive to a period of weight loss or c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
81
0
7

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(94 citation statements)
references
References 52 publications
6
81
0
7
Order By: Relevance
“…CR is known to inhibit in ammatory responses and to improve immunity [47,48]. Prior studies have indicated that CR inhibited critical pathways involved in cytokine and chemokine signaling to reduce the level of circulating pro-in ammatory cytokines, such as TNFα, IL-6, and IL-1β [53][54][55][56][57][58]. Healthy individuals undergoing short-term CR have been shown to have reduced monocyte metabolic and in ammatory activity and a drastic decrease in circulating and organ monocyte numbers [59,60].…”
Section: Discussionmentioning
confidence: 99%
“…CR is known to inhibit in ammatory responses and to improve immunity [47,48]. Prior studies have indicated that CR inhibited critical pathways involved in cytokine and chemokine signaling to reduce the level of circulating pro-in ammatory cytokines, such as TNFα, IL-6, and IL-1β [53][54][55][56][57][58]. Healthy individuals undergoing short-term CR have been shown to have reduced monocyte metabolic and in ammatory activity and a drastic decrease in circulating and organ monocyte numbers [59,60].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in agreement with the findings by Dela et al, a much stricter intervention in terms of nutritional control and exercise is required to reduce LDL cholesterol. That this is achievable has been shown by the Calerie studies . Nevertheless, as reported by Dela et al the improvements in insulin sensitivity may be only transient when the intervention includes only a caloric restriction, while it may be sustained when the intervention includes a substantial amount of exercise together with dietary control in type 2 diabetics…”
mentioning
confidence: 81%
“…That this is achievable has been shown by the Calerie studies. 18,19 Nevertheless, as reported by Dela et al 14 the improvements in insulin sensitivity may be only transient when the intervention includes only a caloric restriction, 19 while it may be sustained when the intervention includes a substantial amount of exercise together with dietary control in type 2 diabetics. 16 Overall, as reported for several chronic diseases, exercise helps to improve several psychosocial aspects of life, while it slows down the aging-associated decline in motor functions.…”
mentioning
confidence: 94%
“…In clinical settings, caloric restriction and fasting has been documented to improve several cardiometabolic risk factors in nonobese humans. [16] This healing effect is medicated through a wide range of mechanisms such as modification of blood pressure, resting heart rate, levels of high-density and low-density lipoprotein (HDL and LDL) cholesterols, triglycerides, glucose, and insulin concentration, and insulin resistance. [16][17][18] Besides, atherosclerosisassociated systemic inflammation and oxidative stress markers can be significantly reduced in fasting.…”
mentioning
confidence: 99%
“…[16] This healing effect is medicated through a wide range of mechanisms such as modification of blood pressure, resting heart rate, levels of high-density and low-density lipoprotein (HDL and LDL) cholesterols, triglycerides, glucose, and insulin concentration, and insulin resistance. [16][17][18] Besides, atherosclerosisassociated systemic inflammation and oxidative stress markers can be significantly reduced in fasting. [19,20] Fasting can also protect individuals against malignancies.…”
mentioning
confidence: 99%